2018
DOI: 10.1155/2018/1497097
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Mevalonate Pathway in Rat Splenic Lymphocytes: Possible Role in Cytokines Secretion Regulated by L-Theanine

Abstract: L-Theanine is a nonprotein amino acid in tea, and its immunomodulatory function has been confirmed. This study aimed to investigate the effect of L-theanine addition on cytokines secretion in rat splenic lymphocytes and explore its potential immunomodulatory effects on the mevalonate biosynthetic pathway. Our results showed that L-theanine treatment did not influence the proliferation and division indexes of the splenic lymphocytes subsets. Interestingly, L-theanine treatment had regulated the contents of IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition, Rap1A and HMGCR protein expression was positively correlated with IFN-γ, IL-4, and IL-6 levels. These results suggested that L-theanine may regulate cytokine secretion in rat splenic lymphocytes by activating the expression of Rap1A and HMGCR proteins involved in the mevalonate biosynthesis pathway [62].…”
Section: Regulation Of Cytokines and Neurotransmittersmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, Rap1A and HMGCR protein expression was positively correlated with IFN-γ, IL-4, and IL-6 levels. These results suggested that L-theanine may regulate cytokine secretion in rat splenic lymphocytes by activating the expression of Rap1A and HMGCR proteins involved in the mevalonate biosynthesis pathway [62].…”
Section: Regulation Of Cytokines and Neurotransmittersmentioning
confidence: 85%
“…The intake of alkylamines through diet (L-theanine) and medicines (such as bisphosphonates) inhibits the MEP and increases the accumulation of IPP so that Vγ2Vδ2T cells are in the primed and ready state, which can rapidly respond and proliferate in the face of pathogens and expand up to 50 times in the peripheral blood [53]. It has also been proven that L-theanine regulates the secretion of cytokines in spleen lymphocytes by activating the expression of Rap1A and 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) proteins in the MEP and is a promising immunostimulant [62].…”
Section: Activation Of γδT Lymphocyte Functionmentioning
confidence: 99%
“…In the SD rat models, daily intragastric administration of L-theanine solution (400 mg/kg) could increase the weight of the spleen, modify the balance of Th1/Th2 cytokines, reduce the level of serum corticosterone, increase the level of dopamine and 5-HT in the brain, and regulate the mRNA expression of phospholipase C isomers in the heart, finally improving the immune function ( 92 ). Moreover, in another study, L-theanine effectively regulated the secretion of cytokines such as IFN-γ, IL-2, IL-4, IL-10, IL-12, and TNF-α except for IL-6 by activating the mRNA and protein expression of Ras-related protein Rap-1A (Rap1A), 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), and farnesyl diphosphate synthase (FDPs) in the mevalonate synthesis pathway of rat splenic lymphocytes ( 93 ). In addition, L-theanine treatment decreased the mRNA expression of Toll-like receptors (e.g., TLR-2 and TLR-4) and cytokines (e.g., IFN-α, IFN-γ, and IL-2) in broilers ( 94 ).…”
Section: Health Benefits Of L-theaninementioning
confidence: 99%
“…10 Along with other phytochemicals in green tea, Ltheanine also shows attractive biological activities, such as antiaging, antianxiety, anticancer, anti-inflammatory, antimicrobial, antioxidant, growth-promoting, and hepato-protective activities. 11 Regarding the immune system, L-theanine is involved in enhancement of γδ T-cell function, 12,13 improvement of Th1/Th2 cytokine balance, 14 regulation of cytokine secretion, 15 and control of immune function by binding to cannabinoid receptor. 16 However, both the physiological effects of L-theanine on the immune system and its action mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%